Content Analysis of Trends in Print Magazine Tobacco Advertisements - Banerjee, Smita (Tob Regul Sci, 2015)
OBJECTIVES: To provide a descriptive and comparative content analysis of tobacco print magazine ads, with a focus on rhetorical and persuasive themes. METHODS: Print tobacco ads for cigarettes, cigars, e-cigarettes, moist snuff, and snus (N = 171) were content analyzed for the physical composition/ad format (e.g., size of ad, image, setting, branding, warning label) and the content of the ad (e.g., rhetorical themes, persuasive themes). RESULTS: The theme of pathos (that elicits an emotional response) was most frequently utilized for cigarette (61%), cigar (50%), and moist snuff (50%) ads, and the theme of logos (use of logic or facts to support position) was most frequently used for e-cigarette (85%) ads. Additionally, comparative claims were most frequently used for snus (e.g., “spit-free,” “smoke-free”) and e-cigarette ads (e.g., “no tobacco smoke, only vapor,” “no odor, no ash”). Comparative claims were also used in cigarette ads, primarily to highlight availability in different flavors (e.g., “bold,” “menthol”). CONCLUSIONS: This study has implications for tobacco product marketing regulation, particularly around limiting tobacco advertising in publications with a large youth readership and prohibiting false or misleading labels, labeling, and advertising for tobacco products, such as modified risk (unless approved by the FDA) or therapeutic claims.